Immunoproteomic Approach of Extracellular Antigens From Paracoccidioides Species Reveals Exclusive B-Cell Epitopes - Moreira, André Luís Elias; Oliveira, Milton Adriano Pelli; Silva, Lana O’Hara Souza; Inácio, Moisés Morais; Bailão, Alexandre Melo; Parente-Rocha, Juliana Alves; Cruz-Leite, Vanessa Rafaela Milhomem; Paccez, Juliano Domiraci; de Almeida Soares, Célia Maria; Weber, Simone Schneider; Borges, Clayton Luiz (Frontiers in Microbiology, 2020)
Fungi of the Paracoccidioides genus are the etiological agents of Paracoccidioidomycosis (PCM), a systemic mycosis restricted to the countries of Latin America. Currently the Paracoccidioides complex is represented by P. lutzii, P. americana, P. brasiliensis, P. restrepiensis and P. venezuelensis. Even with advances in techniques used for diagnosing fungal diseases, high rates of false-positive results for PCM are still presented. Additionally, there is no efficient antigen that can be used to follow-up the efficiency of patient treatment. The immunoproteomic is considered a powerful tool for the identification of antigens. In addition, antigens are molecules recognized by the immune system, which make them excellent targets for diagnostic testing of diseases caused by microorganisms. In this vein, we investigated which antigens are secreted by species representing Paracoccidioides complex in order to increase the spectrum of molecules that could be used for future diagnostic tests, patients follow-up, or PCM therapy. To identify the profile of antigens secreted by Paracoccidioides spp., immunoproteomic approaches were used combining immunoprecipitation, followed by antigen identification by nanoUPLC-MSE based proteomics. Consequently, it was possible to verify differences in the exoantigen profiles present among the studied species. Through a mass spectrometry approach it was possible to identify 79 exoantigens in Paracoccidioides species. Using bioinformatics tools, two unique exoantigens in P. lutzii species were identified, as well as 44 epitopes exclusive to the Paracoccidioides complex and 12 unique antigenic sequences that can differentiate between Paracoccidioides species. Therefore, these results demonstrate that Paracoccidioides species have a range of B-cell epitopes exclusive to the complex as well as specific to each Paracoccidioides species. In addition, these analyses allowed us the identification of excellent biomarker candidates for epidemiology screening, diagnosis, patient follow-ups, as well as new candidates to PCM therapy.